Synthesis of enantiomerically pure helicene like bis-oxazines from atropisomeric 7,7’-dihydroxy BINOL: Preliminary measurements of the circularly polarized luminescence - Sundar, M. Shyam (2014)
[Image: see text] Racemic sample of 2,2’,7,7’-tetrahydroxy-1,1’-binaphthyl was resolved with (S)-proline and the separated enantiomers were independently converted to atropisomeric bis-oxazines by aromatic Mannich reaction. These chirally pure oxazines were then converted to the helicene like cyclic ethers. The Circularly Polarized Luminescence (CPL) profile was consistent with the isolation of the targeted helical-like molecules in optically pure form, prepared from the achiral primary amines. The compounds of interest displayed active and opposite CPL activities for each sets of the helicene like isomers (P)-/(M)-3 and (P)-/(M)-5.